Prediksi Harga Beras di Provinsi Nusa Tenggara Barat Dengan Metode Least Square Approximation - Anjani, Aulia Fadma; Choirunnisa, Nabila; Haizar, Maulana Rifky; Robbaniyyah, Nuzla Af’idatur; Rusadi, Tri Maryono (Puslitbang Sekawan Institute Nusa Tenggara, 2025)
The Linear Least Square Approximation method is applied to predict rice prices in West Nusa Tenggara (NTB) Province. The price of rice plays a strategic role in the Indonesian economy as it is the basic need of most people, and its fluctuations have a significant impact on purchasing power and economic stability. Various factors influence changes in rice prices, such as production volume, climate conditions, and the possibility of price manipulation by certain parties. In this analysis, the Least Square Approximation method was chosen because it is able to capture trend patterns based on historical data from 2015-2022 obtained from the Central Statistics Agency (BPS), thus helping to project future prices. The prediction results show that rice prices in the period tend to be stable in the range of IDR 8,900 to IDR 9,800 per kilogram. The accuracy of the model was evaluated using Mean Absolute Percentage Error (MAPE), which resulted in an error of 2.59%, indicating that the method is effective and reliable enough to provide accurate rice price predictions.